User Experiences of Electronic Controlled Substance Surveillance Among Health Care Professionals in a Large Academic Hospital: Cross-Sectional Survey - Annika Häkkinen; Hanna M Tolonen; Tinja Lääveri; Johanna Viitanen; Kaisa Savolainen; Mia Sivén (Journal of Medical Internet Research, 2026)
Abstract Background Controlled substances are commonly used as analgesics or to treat neurodevelopmental disorders in health care, but they also pose a risk of drug abuse and diversion. Therefore, the distribution and handling of controlled substances are strictly regulated, and hospital pharmacies are required to manage their surveillance in hospital settings. Between 2018 and 2021, a large Finnish academic hospital implemented a new electronic health record system enabling the digitalization of paper-based controlled substance surveillance. By November 2023, the electronic narcotic consumption card (eNCC) had been implemented in 84 wards. Although hundreds of health care professionals (HCPs) use the eNCC daily, our understanding of the user experience (UX) with this process is limited. Objective This study aimed to characterize UX with the eNCC and compare it across different dosage forms. Additionally, we aimed to assess whether the end user’s professional role, years in practice, and years of electronic health record system use affect UX and how investigations and error corrections in controlled substance surveillance have evolved since the implementation of the eNCC. Methods An electronic survey was conducted among HCPs working in wards and the hospital pharmacy in May 2024. The survey included background questions, statements using a 5-point Likert scale, and 1 open-ended question. This study was reported in accordance with the CROSS (Consensus-Based Checklist for Reporting of Survey Studies) guidelines. Results There were 599 respondents (n=522, 87.1% nurses; n=21, 3.5% physicians; n=56, 9.3% pharmacists) to the survey during the 3-week response period. Our main finding was that HCPs preferred the eNCC process; 80.9% (484/598) of respondents disagreed when asked whether they were willing to return to the paper-based process. Additionally, HCPs considered the eNCC to be effortless in daily work for both solid (491/578, 84.9%) and liquid (418/578, 72.3%) dosage forms. However, the eNCC process for solid dosage forms was reported to be more straightforward and faster than that for liquid ones. Both nurses and pharmacists reported conducting more investigations and error corrections immediately after eNCC implementation than during the most recent month. Nevertheless, ward pharmacists performed more investigations and corrections than registered nurses at both specified time points. Conclusions Most HCPs had rather positive attitudes toward the eNCC, and they preferred it over a paper-based process. This research highlights the importance of understanding the varying levels of interaction with the eNCC among different professional roles.